634. PERIOPERATIVE MORBIDITY AND MORTALITY AFTER STANDARD TWO-FIELD AND RADICAL THREE-FIELD ESOPHAGECTOMY – RESULTS FROM A RANDOMIZED TRIAL. (24th September 2022) - Pramesh, CS; Karimundackal, George; Jiwnani, Sabita; Shetmahajan, Madhavi; Ranganathan, Priya; Parab, Swapnil; Niyogi, Devayani; Tiwari, Virendra; Mistry, Rajesh; Badwe, Rajendra
Abstract: The role of radical lymphadenectomy in esophageal cancer is controversial. While standard two-field lymph node dissection (2FLND) is considered the standard of care, the role of prophylactic radical three-field lymph note dissection (3FLND) is debatable. We conducted a large randomized trial comparing oncological outcomes between 2FLND and 3FLND for operable esophageal cancer. Here, we report the perioperative complications in the trial. Patients with operable esophageal squamous cell/adenocarcinoma between 18-75 years of age with no clinicoradiological supracarinal lymph node metastases were eligible. Patients were randomly allocated intraoperatively with allocation concealment (stratified by histology, T, N stage, level of growth, and neoadjuvant treatment) to 2FLND or 3FLND. Patients randomized to 2FLND underwent removal of all infracarinal mediastinal and D2 abdominal lymph nodes; patients randomized to 3FLND in addition had bilateral supracarinal mediastinal and lower cervical neck lymph node dissection. Intraoperative and postoperative details including perioperative complications were collected. Chi-square test was used for categorical and the Student t test for numeric variables. A total of 700 patients were recruited between Jan 2005 and Dec 2019 (359 2FLND, 341 3FLND). Demographic data are presented in the Table. More patients undergoing 3FLND required prolonged ventilation (4.2 vs 12%, p<0.001), had pulmonary complications (25.6 vs 38.1%, p<0.001) and anastomotic leaks (11.7% vs 17.6%, p=0.03). There were no differences in cardiac complications (0.8 vs 2.6%, p=0.08), chyle leaks (3.1 vs 3.5%, p=0.83), major morbidity (CD score >3a; 14.8% vs 19.4%, p=0.13) and mortality (4.5 vs 5.9%, p=0.4) in the two groups. Pulmonary complications and anastomotic leaks occur more frequently with 3FLND than 2FLND while major morbidity and mortality were similar. Oncological outcomes will dictate whether 3FLND is beneficial in patients with operable esophageal cancer.